Analisa Potensi Ekonomi Daerah Dalam Rangka Penyusunan Kebijakan Pembangunan RPJMD Kabupaten Pasaman Tahun 2021-2026 - Lusi Dewiana (Pusdikra-Publishing.com, 2022)
The results of the calculation of the LQ of the three basic sectors show a stable value from 2016 to 2020, where the Agriculture, Forestry and Fisheries Sector is stable above 2 (two), the Water Supply Sector, Waste Management, Waste and Recycling and the Government Administration Sector, Defense and Mandatory Social Security are stable above number 1 (one) The three basic sectors obtained are relevant to the mission of the Regional Head, namely the Agriculture, Forestry and Fisheries Sector which is relevant to mission 5